Case Report: Freeze-Dried Human Amniotic Membrane Allograft for the Treatment of Chronic Wounds: Results of a Multicentre Observational Study - Schmiedova, Iveta; Ozanova, Zuzana; Stastna, Elen; Kiselakova, Ludmila; Lipovy, Bretislav; Forostyak, Serhiy (Frontiers in Bioengineering and Biotechnology, 2021)
An inability of the human body to heal acute wounds under certain conditions results in the formation of chronic ulcers. Chronic wounds not only cause significant pain and discomfort for patients but also serve as an entry for pathogens into the human body, which can result in a serious life-threatening problem. Due to limited therapeutic possibilities for chronic wounds, it is a significant burden for the patients and society. Current work present results of a multicentre observational study demonstrating the use of a lyophilized amniotic membrane (AM) in the treatment of chronic wounds (various aetiologies). Lyophilized amniotic membrane produced under the commercial brand Amnioderm®. A novel allograft material was applied for therapy of chronic wounds when the standard of care (SoC) for the chronic ulcers had failed. The wounds considered for the application of AM were in the duration range between 2 months and 11 years. Of the total of 16 enrolled patients, 8 patients were completely healed, 6 patients demonstrated significantly reduced ulcer size and 2 subjects did not respond to the AM therapy. Current study unambiguously demonstrates an effective alternative to the standard of chronic wounds care and confirms a significant effect of the Amnioderm® application for chronic wound management as a new standard of care.